Trip generation rate of fast-food restaurants in Johor Bahru area - Ahmed Abdulameer Hussein, 1983-; Ishtiaque Ahmed, supervisor; Fakulti Kejuruteraan Awam (2013)
Thesis (Sarjana Kejuruteraan (Awam - Pengangkutan dan Jalanraya)) - Universiti Teknologi Malaysia, 2013